Dribbling Training Methods 15 yard Turn and 20 yard Squared For Improving Results Undikma Football - Susi Yundarwati; Intan Primayanti (Universitas Suryakancana, 2021)
The aim is to see the effect of the 15 yard turn and 20 yard squared dribbling training methods on the improvement of UNDIKMA football dribbling results, lacking in terms of agility, speed and balance, when dribbling. The design method used in this study is a design or design with an experimental model. This type of research uses the Experiment